Investigation of singularities inherent to Mueller matrix images of biological crystals: diagnostics of their birefringent structure - Misevitch, I.Z.; Ushenko, Yu.O.; Pridiy, O.G.; Motrich, A.V.; Tomka, Yu.Ya.; Dubolazov, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
In this work, we have theoretically grounded conceptions of singularities observed in coordinate distributions of Mueller matrix elements for a network of human tissue biological crystals. Found is interrelation between polarization singularities of laser images inherent to these biological crystals and characteristic values of above matrix elements. We have determined criteria for statistical diagnostics of pathological changes in the birefringent structure of biological crystal network by using myometrium tissue as an example.